Recent Trends in Digital Marketing to Develop the Marketing Strategies for Every Marketer - Memon, U. Y.; Khandre, Yogesh (Asian Journal of Engineering and Applied Technology, 2020)
The overall marketing situation is rapidly converting over the last few years. With this modification it has a positive impact on the developing economies. Moreover this has led to high general of living, excessive in step with capita income and thereby contributing to the economic development. It is now not a seller’s market and over the years, it has emerge as one of the largest customer markets within the world. Today, the market for the developing economies is based totally on the right competition principle with the presence of both buyers and sellers. Therefore purpose of this paper is, first, to review and recognize standards of digital marketing secondly, to speak about various present day developments in digital advertising and marketing and, lastly, to talk about and summarize the destiny of digital advertising and marketing.